SIMULTANEOUSLY T TRAINING IT IMPROVES ADAPTATIONS NEURAL IN BEGINNING IN THE PRACTICAL ONE OF PHYSICAL EXERCISE (Fiep Bulletin - online, 2014)
The main research regarding the simultaneously training that associates the aerobic exercise to the resisted exercise in the same section of training this investigates neural and morphology adaptations. This study to has as its main objective analyze the effect of the simultaneously training in the activation and muscle co-activation when compared with the specific Force Training. It study was formed by 12 males: group Training Force (TF) n = 6, average age 28,5 years (+9,46); group Simultaneously Training: (TC) n = 6, average age 28,5 years (+8, 63), For collection of data used circumference of the arm, (?) (DC) of tríceps and biceps, test of relative force, Eletromiophy de periphery For treatment of the data SPSS 11-5 with significance was used statistics (p
Keywords: Resisted Exercise; Aerobic Exercise; Eletromiophy for Perifery